Information and Legislative Bargaining: The Political Economy of U.S. Tariff Suspensions - Ludema, Rodney D.; Mayda, Anna Maria; Mishra, Prachi (The Review of Economics and Statistics, 2018)
This paper studies the political influence of individual firms on congressional decisions to suspend tariffs on U.S. imports of intermediate goods. We develop a legislative bargaining model in which firms influence legislators by transmitting information about the value of protection, using verbal messages and lobbying expenditures. Model estimation using firmlevel data on tariff suspension bills and lobbying expenditures reveals that the probability a suspension is granted decreases with each additional firm that expresses opposition. This effect is significantly larger than that of either opponent or proponent lobbying due to the greater information content of verbal opposition and legislative bargaining costs.